Synthesis, characterization, and property of ionized nano‐objects with defined phase separation. Issue 7 (13th December 2022) - Li, Penghan; Zhou, Peng; Wang, Jian; Wang, Guowei
Abstract: The ionized nano‐objects with defined microphase separation were prepared and properties were investigated. Firstly, the polyisoprene‐ b ‐polystyrene (PI‐ b ‐PS) based nano‐objects were prepared through living anionic polymerization‐based polymerization‐induced self‐assembly (LAP‐PISA) technique, and the nano‐objects were in‐situ stabilized by divinylbenzene (DVB) agent. Subsequently, the PI segment on nano‐objects or (co)polymers was sequentially brominated and ionized, and the ionic pairs were introduced. The successful synthesis of the nano‐objects and the subsequent modification were comprehensively verified by multiple measurements. Furthermore, the thermal property of the nano‐objects or (co)polymers was investigated by thermogravimetric analysis (TGA) and differential scanning‐calorimetry (DSC) measurements, and the electric property was evaluated by impedance analyzer. The ionic conductivity ( σ ), relative permittivity ( ε r ) and dielectric loss (tg δ ) of ionized nano‐objects were compared with the counterparts of ionized, linear PI‐ b ‐PS and PI. The results showed that the introduction of PS segment could strengthen the ionic system, and however, reduce the electric property. With the same composition, the ionized nano‐objects should have more regular microphase separation and transportation channels for ions than that for the linear PI‐ b ‐PS copolymer. The σ for the former was five times of that for the latter. Abstract :